PENGARUH PENDIDIKAN KESEHATAN DENGAN PENGETAHUANTENTANG 3M DALAM PENCEGAHAN COVID-19 PADA SISWA DI SMAN 6 KOTA TANGERANG - Alif Nurul Rosyidah (STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Corona Virus Disease (COVID-19) is an infectious disease caused by a new type of corona virus, where the number of cases and deaths is increasing every day. The spread of the virus must be stopped immediately, the government has implemented various health policies. One of the preventions is implementing 3M (washing hands, keeping a distance and wearing a mask). This study aims to determine the effect of health education with knowledge of 3M in preventing COVID-19 among high school students in Tangerang City. Methods: This study used a quasi-experimental pre-post test design with a control group. The sample of this study was students with a total of 30 respondents for two groups (intervention group = 15 and control group = 15). Result: the research shows that there is an effect of health education with knowledge about 3M in preventing COVID-19 in high school students in Tangerang City with p = 0.000. Conclusion: There is an influence of health education with knowledge of 3M in preventing COVID-19 among high school students in Tangerang City